Obstacles Facing Faculty Members in Sana'a Community College from their Perspective - Raheeb Saeed Kaid Al-Absi (University of Science and Technology, Yemen, 2021)
The study aimed to identify the obstacles that faculty members face at Sana'a Community College. To achieve the objectives of the study, the researcher used the analytical descriptive method and the questionnaire as a tool for collecting data. The study population consisted of (176) faculty members. As the population was small, the sample was selected by the complete census method. The study results showed that the most important academic constraints were absence of support for conducting research, lack of department support to participate in courses, seminars and conferences and scarcity of training programs. The most important financial and administrative constraints were lack of adequate attention to the problems of faculty members, lack of suitable places to practice scientific activities, and absence of incentives for distinguished faculty member. The most important obstacles associated with students were low background level of accepted students, lack of clear syllabus for courses, and the reluctance of students to research and refer to scientific references. The most important technical constraints facing faculty members were lack of participation in academic sites, lack of appropriate learning resources, permanent power cut-offs in classrooms and laboratories and lack of printing and photocopy machines for the faculty members when needed. The study also showed that there were no statistically significant differences between the responses of faculty members about the obstacles due to variables of gender, academic rank and years of experience. The study recommended providing material and moral support to faculty members to conduct research, holding training courses to raise their efficiency, taking care of their own financial aspects and involving them in important decisions related to the educational process, applying appropriate criteria for admitting students, avoiding favoritism, paying attention to updating study plans, and providing recent references. Keywords: obstacles, faculty, community college.